Preoperative Predictors and Ossicular Involvement in Chronic Otitis Media - Mohan Ananthula; Soumya Singh (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: Ossicular chain disease may occur in chronic otitis media (COM). Certain preoperative factors can predict this ossicular disruption, which can be confirmed intraoperatively and can prognosticate the surgical outcome in COM. Material and methods: One hundred and forty-five patients of COM were recruited in this prospective study, and ossicular chain status in different types of COM was studied and compared. All the variables were noted, and statistical analysis was performed using IBM (International Business Machines) SPSS (Statistical Package for the Social Studies) Statistics 26 software. Results: Intra-operatively ossicular chain defects were detected in 48(33.1%) cases. Of these, Incus (32.41%) was found to be the most common, followed by malleus (20.7%) and less commonly stapes (9.66%). The most common type of ossicular erosions seen in our study was the M+ Ip S+ (Malleus intact, Incus partially eroded, and Stapes intact) type seen in 13 cases. The mean hearing loss was higher (54.96dB) in patients with ossicular erosion compared with patients without ossicular erosion (41.30dB). Conclusions: Moderate to severe hearing loss and air-bone gap of >40dBand active squamosal type of COM (cholesteatoma) are the important predictors of ossicular chain disease in COM. Ossicular chain disruption can be classified according to the involvement of different ossicles and can help to prognosticate the postoperative outcome.